Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1161/circimaging.119.010287
|View full text |Cite
|
Sign up to set email alerts
|

Global Left Atrial Longitudinal Strain Using 3-Beat Method Improves Risk Prediction of Stroke Over Conventional Echocardiography in Atrial Fibrillation

Abstract: Background: Atrial fibrillation (AF) is associated with a risk of ischemic stroke, and functional myocardial imaging has offered novel insights on its pathophysiology and prognosis, but its use in AF-related stroke remains limited. We aimed to evaluate the feasibility of left atrial (LA) deformations and its prognostic values of ischemic stroke in a large-scale AF population. Methods: Peak atrial longitudinal strain (LA strain), left ventricular strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…In addition, ACM might be important in patients with stroke (King et al, 2017;Muller et al, 2018). This might also explain that a very recent study by Liao et al (2020) demonstrated that reduced LASr (measured during AF) enabled identification of patients at risk for future ischemic stroke (Liao et al, 2020). This underlines the importance of valid non-invasive screening methods in order to identify patients at risk as early as possible and to prevent ACM-associated complications.…”
Section: Atrial Cardiomyopathy Atrial Fibrillation and Heart Failurementioning
confidence: 98%
“…In addition, ACM might be important in patients with stroke (King et al, 2017;Muller et al, 2018). This might also explain that a very recent study by Liao et al (2020) demonstrated that reduced LASr (measured during AF) enabled identification of patients at risk for future ischemic stroke (Liao et al, 2020). This underlines the importance of valid non-invasive screening methods in order to identify patients at risk as early as possible and to prevent ACM-associated complications.…”
Section: Atrial Cardiomyopathy Atrial Fibrillation and Heart Failurementioning
confidence: 98%
“…Several studies regarding the potential role of LA strain in stroke risk stratifications have been published and summarized in Figure 4 . 50) 51) 58) A lower LA strain is commonly observed in AF patients irrespective of different age strata compared to normal subjects, 58) and independently associated with an increasec risk of ischemic stroke (7.8% lower risk of stroke per 1% increase in LA strain). 50) The degree of decrease of each AF individual's LA strain from reference values can be applied in a stratified manner as standard score for organized risk stratification.…”
Section: The Future: Atrial Fibrillation Duration and Left Atrial Functionmentioning
confidence: 99%
“… 50) 51) 58) A lower LA strain is commonly observed in AF patients irrespective of different age strata compared to normal subjects, 58) and independently associated with an increasec risk of ischemic stroke (7.8% lower risk of stroke per 1% increase in LA strain). 50) The degree of decrease of each AF individual's LA strain from reference values can be applied in a stratified manner as standard score for organized risk stratification. 51) In the previous study performed by Liao et al, 51) AF patients with a mean LA strain lower than reference values (mean values of LA strain of healthy subjects) for more than 3 standard deviations were associated with a more than 2-fold higher risk of ischemic stroke compared to those whose LA strain was lower for only 2–3 standard deviations.…”
Section: The Future: Atrial Fibrillation Duration and Left Atrial Functionmentioning
confidence: 99%
See 2 more Smart Citations